Paid Surrogacy as a Relational Autonomy Reproductive Labour - Baiocco, Elisa (Socialinė teorija, empirija, politika ir praktika, 2026)
This paper connects paid surrogacy to relational autonomy and reproductive labour, arguing that paid surrogacy requires a regulation that acknowledges and enhances its relational dimension, thus improving the quality of relationships established within surrogacy arrangements. In doing so, it discusses the feminist viewpoints on paid surrogacy. After shedding light on the gender-based potentialities and criticalities of the practice, the article focuses on the feminist debate on the authenticity of women’s consent to engage in paid surrogacy, arguing for the need to prioritise the relational understanding of autonomy. Relational autonomy allows for the contextualisation of the surrogate’s decision (without questioning it) in the light of the gendered, ethnic and economic asymmetries in which she is situated. Building on this perspective, the article explores relational autonomy as an interpretative framework for understanding paid surrogacy as reproductive labour. What is contended is that the stigma attached to the practice (and the resulting altruistic narratives), as well as the neoliberal and globalised dynamics underpinning surrogacy markets, are pivotally important elements to contextualise surrogates’ decisions. This implies assessing the quality of the relationships between the surrogacy agreement parties and elaborating on solutions to improve them. The final part of the paper, indeed, offers some regulatory considerations that do not aim to provide definitive legal solutions, but rather to open a discussion on key aspects that legislators should take into account. Specifically, it is pointed out that the surrogate should enjoy the right to change her mind (since pregnancy is a care relationship that may generate a maternal bond), that multi-parenthood should be implemented (not to exclude intended parents from the reproductive process they had initiated), and that the surrogacy agreement parties should live nearby (in order to facilitate these relational dynamics).